Value of FT3/FT4 Ratio in Prognosis of Patients With Heart Failure: A Propensity-Matched Study - Wang, Chuanhe; Han, Su; Li, Ying; Tong, Fei; Li, Zhichao; Sun, Zhijun (Frontiers in Cardiovascular Medicine, 2022)
Aims Abnormal thyroid hormone secretions can alter the manifestation and prognosis of cardiovascular disease. To assess the effect of the free triiodothyronine (FT3)/free thyroxine (FT4) ratio on the prognosis of patients with heart failure (HF), we performed a propensity-matched study on patients with well-balanced baseline characteristics. Methods Overall, 8,887 patients with HF were divided into two groups according to the FT3/FT4 ratio. Propensity scores were calculated from each patient. A cohort comprising 2,164 pairs with high or low ratios and with 34 well-balanced baseline characteristics was then assembled. The endpoints were Cardiovascular (CV) mortality and all-cause mortality. The correlation between FT3/FT4 ratio and prognosis was assessed using matched Cox regression analyses. The mean follow-up was 3.3 years. Results In the full pre-match cohort, 3,710 (41.7%) patients died, with 2,581 (29.0%) cases of CV mortality. In the matched-pair cohort, all-cause mortality occurred in 923 (1,238/10,000 person-years of follow-up) patients with a high ratio and 1,036 (1,484/10,000 person-years) patients with a low ratio, resulting in a matched HR of 0.841 (95% CI: 0.769–0.919; P < 0.001). For CV mortality, the result was 638 (856/10,000 person-years) and 714 (1,023/10,000 person-years) patients, respectively, resulting in a matched HR of 0.844 (95% CI: 0.759–0.940; P < 0.001). Subgroup analysis revealed that a low FT3/FT4 ratio had a greater predictive value for all-cause and CV mortality in elderly or male patients and in patients with coronary artery disease (CAD), hypertension, diabetes mellitus, HFmrEF, or HFpEF. Conclusions A low FT3/FT4 ratio is valuable for predicting CV mortality and all-cause mortality in patients with HF.